Academic Benefits of an Inclusive and Diverse Social Studies Curriculum - Leow, Caitlin (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Discussions about racism and the history of systemic oppression of minority populations in the United States is being legislated out of classrooms in many states. The purpose of this manuscript is to argue there are academic benefits for students who are exposed to learning about racism and diversity in the classroom. The studies examined follow outcomes from ethnic studies classes and are limited in their sample size and scope. The existing research is minimal, and this manuscript makes a case for continued research of the impacts of ethnic studies classes and classrooms that address racism and systemic oppression. The research presented about students exposed to information about racism and diversity, shows promising results of academic and civic participation benefits for all students.